Incidence of Amblyopia in Strabismic Population - Tayyaba Gul, Mian M. Shafique, Naeem Ullah, Nadeem H. Butt, Muhammad Khalil (Pakistan Journal of Ophthalmology, 2007)
Purpose: To find the incidence and density of amblyopia with reference to the type of squint among the strabismic patients visiting eye department. Material and Methods: This prospective study was started in January 2000 and a total of 177 patients have been dealt with. Both male and female patients of all age groups and all types of squints were included. All the patients underwent standard procedure of assessment including history, examination and investigations to find the type of deviation, amount of the deviation, the presence of amblyopia and the depth of amblyopia. It was then followed by analysis to see the effect of different factors on the depth of amblyopia Results: Out of 177 patients 94 had uniocular squint (Group-I) and 83 alternating squint (Group-II). Majority of patients in Group-I had some degree of amblyopia (82%). Amblyopia was much less in group-II (18%). All the 106 patients having amblyopia showed at least two lines difference of Snellen’s Acuity between both eyes. Amblyopia is relatively denser in uniocular than alternating strabismus. It is more common and dense in esotropia than exotropia. Conclusion: Strabismic amblyopia is a condition of arrested development of vision due to misalignment of visual axis in the first 5-6 years of life. This can be avoided if it is treated at the right time. Earlier detection and treatment of squint in the amblyogenic years can save the patient from this life long disability.